Decision Making Biases in using Sequence Logo Visualization - Lee, Nung Kion; Yin, Bee Oon (2012)
Sequence Logo is a visualization method for displaying conservations characteristics of a sequence (DNA, RNA, proteins) motif profile obtained from either wet-lab or computational analysis. Usage of visualization in decision making carries some elements of subjectivity. In addition, people’s decisions are often biased in favor of their proposed hypotheses. The objectives of this paper were to examine the biases in using sequence logo as an evaluation metric for transcription factor analysis and identify some critical weaknesses in sequence logo for possible future improvements. Document analysis and subject matter expert interviews method were used for information gathering. We found that sequence logo has been frequently misused to support the results obtained from computational transcription factor analysis. In addition, we suggest that current sequence logo can be improved in several aspects to support various users' needs and minimize elements of subjectivity in decision making.